Laser powder bed fusion (L-PBF) of Ti–6Al–4V/Ti–6Al–2Sn–4Zr–2Mo and Ti–6Al–4V/γ-TiAl bimetals: processability, interface and mechanical properties - Fan, Haiyang (2023)
Titanium alloys of near-α Ti–6Al–2Sn–4Zr–2Mo (Ti-6242) and intermetallic γ-TiAl (Ti–48Al–2Cr–2Nb) are commonly served as turbine blade materials operating at elevated temperatures. This study investigated the feasibility of using laser powder bed fusion (L-PBF) to fabricate two Ti–6Al–4V-based bimetals, i.e., Ti–6Al–4V/γ-TiAl and Ti–6Al–4V/Ti-6242, which may have great potential for the future manufacturing of aerospace components. Results indicated that the bimetal of Ti–6Al–4V/γ-TiAl was unsuccessfully built despite a gradient interface (∼250 μm) achieved via L-PBF. This failure was attributed to the intrinsic cold cracking of γ-TiAl processed by L-PBF instead of the weak interfacial bonding between the two materials. In comparison, another pair of bimetal, Ti–6Al–4V/Ti-6242, was manufactured successfully by L-PBF, resulting in a solid and defect-free interface. Horizontal tensile tests were conducted, and the ultimate strength of the bimetal Ti–6Al–4V/Ti-6242 was 1314 ± 21 MPa. However, compared to single materials, the elongation of the bimetal was lowered to 2.8 ± 0.9% because of the mechanical incompatibility between Ti–6Al–4V and Ti-6242.